Memanfaatkan Bonggol sawi sebagai media pembelajaran dengan teknik mengecap untuk mengembangkan motorik halus pada anak TK negeri Pembina 1 kota jambi - Pajar Sindi Latipatul Hoiro; Salsabila Shahiba Amanullah; Novita Laurent; Nurul Hakiky; Paska Erlinawati Sitinjak; Hendra Sofyan (CV. ITTC INDONESIA, 2024)
Learning Media is very necessary in the world of education. Because it really influences children’s development. It can improve children’s motor development the problem that occurs is that there are still many children who cannot handle natural materials well. To overcome this problem, it can be overcome this problem, it can be overcome by using tasting techniques. Dancing aims to develop the creativity level of children aged 3-4 years. The methods used in this research are observation and documentation. The result of this research are that there are still many children who cannot differentiate colors well. Taste techniques are effective in developing fine motor skills in children.